The Potency of Fire and Explosion Hazard on Premium Oil Storage Tank at Depot X 2007 - Lestari, Fatma; Nurdiansyah, Warid (Makara Journal of Technology, 2007)
The Potency of Fire and Explosion Hazard on Premium Oil Storage Tank at Depot X 2007. Premium oil storage tanks have fire and explosion risk because Premium oil is flammable liquid. Because of that, fire and explosion risk assessment on Premium oil storage tank at Depot X is needed as foundation to fire and explosion risk management, and comply with regulations. Method of this research is Dow’s Fire and Explosion Index. This research indicate that F&EI value for Premium oil storage tank is 118,82. Based on that F&EI value, level of risk at Premium oil storage tank is intermediate risk.